Characteristics of Ba-Doped PbS Thin Films Prepared by the SILAR Method - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2014)
In this material production research, undoped and Ba-doped nanostructured PbS films are fabricated on glass surfaces by SILAR method. The structural, optical and morphological properties of the films are examined via scanning electron microscopy, UV-vis spectrophotometry and X-ray diffraction analysis. Scanning electron microscopy analysis revealed that Ba-doping concentration influences the size of the thin film's nanoparticles. Xray diffraction results showed that all of the thin films are in a face centered cubic structure. Optical studies, in the room temperature, revealed that the optical band gap of the films increases as Ba-doping concentration is increased. The intercept values on the energy axis in the range of 1.86 eV and 2.12 eV for 1% and 8% Ba-doped PbS films respectively. As a result, it is concluded that the structural, optical and morphological properties of the fabricated thin films are directly depend on the Ba doping ratio.
Keywords: IONIC-LAYER ADSORPTION; TRANSPORT-PROPERTIES; DEPENDENT PROPERTIES; OPTICAL-PROPERTIES; DEPOSITION; NANOCRYSTALS; SUBSTRATE; GROWTH